Neo Left Main Channel Creation Using Double Stenting Alongside a Sapien 3 Aortic Valve Bioprosthesis for Left Main Coronary Obstruction Following Valve-in-Valve Transcatheter Aortic Valve Replacement: A Case Report With Review of Literature. (28th March 2018) - Patel, Apurva D.; Haldis, Thomas; Al Balbissi, Kais; Paul, Timir
Transcatheter aortic valve replacement in the setting of failed surgical bioprosthesis (valve-in-valve) is a valuable option for patients with bioprosthetic aortic stenosis or regurgitation who are deemed high risk for repeat open heart surgery. Although the procedure is successful with proper preprocedural assessment, instances of left main (LM) coronary artery ostium obstruction have been documented. We present a case of LM coronary obstruction in the immediate postoperative period following implantation of a 20-mm Edwards Sapien 3 valve inside the degenerated 21-mm Mitroflow bioprosthesis stenosis, which was treated with double stenting alongside the Edwards Sapien 3 valve creating a channel ("neo left main") that extended from mid-LM to the upper margin of the Edwards Sapien 3 valve. Although valve-in-valve in a Mitroflow degenerated bioprosthesis is a relatively safe procedure, 2 or more stents may be necessary to scaffold a channel to the coronary arteries between Edwards Sapien 3 prosthesis and aorta in the event of a coronary obstruction.